ENVIRONMENTAL POLICIES AND FISCAL INSTRUMENTS IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT: AN ANALYSIS OF ENVIRONMENTAL TAXES - Düriye Toprak (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Environmentalproblems that have largest externalities among global commodities and thatcause damages affecting future generations, exceed the limits to be solved bymarket solutions or countries' own efforts. Prevention or reduction of thenegative effects and damages of such externalities is only possible with thesolutions and measures including global business associations, internationalagreements, cooperation and universal approaches. In this context,environmental policies are crucial in terms of achieving sustainabledevelopment and providing concrete environmental improvements. Environmentalproblems and factors such as trying to realize sustainable development withinthese problems have exacerbated the need for regulatory effects ofenvironmental taxes. Environmental taxes are one of the most important fiscalpolicy instrument used in internalizing “negative externalities”.In the study, environmentalpolicies and applied financial instruments are addressed in the framework ofsustainable development; environmental taxes are examined conceptually and interms of scope; and environmental taxes are evaluated comparatively for bothdeveloped countries and Turkey.